Ecce Wahine: Towards a Māori Translation of Western Text - McNamara, Moata (Auckland University of Technology, 2014)
Taking its lead from pūkenga Ngāpuhi Māori Marsden’s (Māori Marsden, 2003) writings relating to Papatūānuku (Motherearth) and Ngā Tawhito (the ancient ones), this thesis seeks a reading of two Western texts that retains Māori customs and philosophy, acknowledging that ‘Western’ and ‘Māori’ are linguistic and cultural constructs that cannot be simplified in opposition. In response to the vast range of artworks addressing the biblical ‘Ecce homo’, Ecce wahine traces a route through images operating at the margins of Jacques Derrida’s chapter ‘A Silkworm of One’s Own: Points of View Stitched on the Other Veil’, and Carl-Theodor Dreyer’s 1927 film The Passion of Joan of Arc. Marginal images perform as sites of possibility for translation, retaining references to Ngā Tawhito, traditionally reserved for readings of Māori text and image from Aotearoa-New Zealand. This thesis also pays respect to Hinengaro (Hidden Maiden), who brings to the surface connections hitherto buried in memory. It prompts discussion on gendered and cultural difference in vision and seeing, naming, signs and signatures, notions of translation, sovereignty, colonization, film, image and text and on the place of Ngā Tawhito in contemporary readings of image. In search of a return home to and through the title, the graphic and visual encounter involving exegesis and exhibition that makes up the thesis moves slowly through a concealing and revealing veil, to approach those gendered and cultural differences. For it is at the site of vision and visibility that (im)possibilities of reading a relationship between Māori and Latin, between film and text, offer a translation in the form of a poetic opening. Such reading(writing) calls for inventions and interventions, for a poetics of mourning to pay respect to the dissimulating veil that hides ways of beholding cultured and gendered difference and attempts to read together two very disparate words; Ecce and Wahine.
Keywords: Translation; Ecce; Wahine